(untitled) (Encuentros, 2025)
This study examines the construct validity and relevance of the categories involved in the UTAUT 2 model in the context of entrepreneurs, aiming to assess whether its concepts are applicable for understanding how this population segment adopts new technologies. Previous technology acceptance models, such as TAM and UTAUT, were primarily designed for employees and consumers, making it an opportunity to conduct a specific analysis to see how they fit the realities of entrepreneurs. Technology plays a key role in the success of entrepreneurial ventures, and entrepreneurs, who often work in dynamic environments, face unique challenges in adopting it. This qualitative and exploratory study is based on interviews with 24 Spanish-speaking entrepreneurs developing startups. From these interviews, the relevance of the various factors in the UTAUT 2 model was analyzed in this group. The results showed that some constructs, such as performance expectancy and effort expectancy, are relevant, while others, such as social influence and habit, play a less significant role for entrepreneurs. Additionally, adaptations to the model are suggested, considering factors such as perceived risk and perceived trust in technology. In conclusion, the applicability of UTAUT 2 to entrepreneurs is discussed, and potential improvements are proposed to better suit the needs of this population segment.